Facile and Green Approach To Fabricate Gold and Silver Coated Superparamagnetic Nanoparticles - Chin, S.F.; K., Swaminathan Iyer; Raston, Colin L. (American Chemical Society, 2009)
Superparamagnetic magnetite nanoparticles are coated with homogeneous gold and silver shells using a simple aqueous based seed mediated method at room temperature with dopamine as a surfactant. Nanoparticles of Au in the range 2-3 nm are attached to amine functionalized Fe3O4 nanoparticles, acting as seed for the growth of ultrathin Au or Ag shells. The monodispersed core-shell nanoparticles Fe3O4@Au and Fe3O4@Ag have a particle size range of 10-13 nm with a shell thickness of approximately 2-3 nm. They are magnetically purified and are superparamagnetic at 300 K with saturated magnetization values of 41 and 35 emu g-1, respectively.